HUBUNGAN POLA ASUH, RIWAYAT ASI EKSKLUSIF, DAN PENGETAHUAN IBU TENTANG GIZI DENGAN PERILAKU PICKY EATING PADA ANAK PRA-SEKOLAH DI RUMAH SUSUN GRIYA TIPAR CAKUNG - Lulu Farwati (2020)
Background: Pre-school age is a critical period in children's growth and development. One of the factors children experiencing growth and development disorders is picky eating. Purpose: Determine the relationship of parenting, history of exclusive breastfeeding, and maternal knowledge about nutrition with picky eating behavior in preschool children in Ruma Griya Tipar, Cakung. Methods: The research method used was quantitative with a cross-sectional design. The research sample was 60 respondents selected with purposive sampling technique. The instrument used in this study was a questionnaire. Results: The results, 48.3% of children with picky eating behavior, 51,7% of parents with poor parenting, 41,7% of children with a history of non-exclusive breastfeeding, and 40% of mothers with low knowledge. Bivariate results performed using the chi-square test show that there is a relationship parenting (p = 0.02) and maternal knowledge about nutrition (p = 0.04) with picky eating behavior in children. Meanwhile, the history of exclusive breastfeeding has no relationship with picky eating behavior in children (p = 0.458). Conclusions: There is a relationship between parenting style and maternal knowledge about nutrition with picky eating behavior in preschool children. There is no relationship the history of exclusive breastfeeding with picky eating behavior in children.